Screening the CLA Producing Lactic Acid Bacteria Isolated from Rumen Goats and Their Effects on Ruminal In Vitro Fermentation - L. A. Oluodo; P. Hnokaew; P. Thirawong; S. Umsook; N. S. Fitriyah; C. Phatsara; C. Lumsangkul; N. Montha; S. Yammuen-Art (Faculty of Animal Science, IPB University, 2026)
Ruminant-Derived products are a major dietary source of conjugated linoleic acid (CLA), a bioactive fatty acid associated with numerous health benefits. However, the natural biosynthesis of CLA in the rumen is often limited by extensive biohydrogenation of unsaturated fatty acids, necessitating strategies to enhance its synthesis through microbial manipulation. This study aimed to identify CLA-producing lactic acid bacteria (LAB) from goat rumen fluid and evaluate their effects on in vitro rumen fermentation characteristics. A total of 140 LAB isolates were obtained from rumen fluid of lactating goats, with 23 isolates demonstrating CLA production ranging from 9.0 to 12.3 μg/mL after 24 h of incubation in MRS broth supplemented with linoleic acid. Molecular identification revealed five unique LAB species: Lactobacillus fermentum (n=15), Lactobacillus plantarum (n=4), Pediococcus acidilactici (n=2), Lactobacillus argentoratensis (n=1), and Lactobacillus pentosus (n=1). L. plantarum-R11 was identified as the highest CLA producer (>12.0 μg/mL) and adopted for in vitro ruminal fermentation assessment. Four treatments: control (TMR), TMR supplemented with L. plantarum-R11 (LP; 10⁸ CFU/mL), TMR supplemented with 2% sunflower oil (SFO), and TMR supplemented with both SFO and LP (LPSFO). The LPSFO group significantly (p<0.05) increased cumulative gas production at 72 h (95.51mL/0.2 g DM) and 96 h (103.47 mL/0.2 g DM) compared to the control. Similarly, the LPSFO group had the highest ammonia-nitrogen content (13.15 mM), while pH remained stable across all treatments. The volatile fatty acid (VFA) profiles, fatty acid profiles, and total ruminal CLA content were similar across treatments. Butyrivibrio fibrisolvens appears more prominent in the LPSFO group on heatmap visualization, a bacterium associated with ruminal biohydrogenation and CLA metabolism. Our findings suggest that L. plantarum-R11 primarily functions as a rumen modulator, influencing rumen microbial ecology and promoting beneficial shifts in microbial community composition that may improve fermentation capacity.